1967
DOI: 10.1017/s0022172400045484
|View full text |Cite
|
Sign up to set email alerts
|

A comparative virological study of children in hospital with respiratory and diarrhoeal illnesses

Abstract: Between October 1963 and April 1965, 113 children with respiratory disease and 113 children with diarrhoeal disease were matched for age and time of entry into hospital and studied by virus isolation and serological techniques.Infections with respiratory syncytial (RS) virus, parainfluenza virus and herpes simplex virus respectively were found in 29, 11 and 12 children in the respiratory illness group but in only 1, 2 and 4 children in the diarrhoeal group. Rhinoviruses were isolated from 10 children in each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1968
1968
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…We have examined stools from babies with enteritis admitted to one ward in one hospital over a period of 16 months. The purpose was to establish what viruses, bacteria and protozoa were excreted by these babies and our findings suggest that, as others have found by cell culture methods (Bell & Grist, 1967;Stott et at. 1967), excretion of viruses in young children does not directly parallel symptoms, and that to regard even rotaviruses as inevitable pathogens may be too simple a view.…”
Section: Introductionsupporting
confidence: 66%
“…We have examined stools from babies with enteritis admitted to one ward in one hospital over a period of 16 months. The purpose was to establish what viruses, bacteria and protozoa were excreted by these babies and our findings suggest that, as others have found by cell culture methods (Bell & Grist, 1967;Stott et at. 1967), excretion of viruses in young children does not directly parallel symptoms, and that to regard even rotaviruses as inevitable pathogens may be too simple a view.…”
Section: Introductionsupporting
confidence: 66%
“…Except in the neonatal period, rotavirus is rarely identified in the stools of asymptomatic children (Albrey and Murphy, 1976;Totterdell et al, 1976;Gust et al, 1977;Murphy et al, 1977) but the same is not true of other stool viruses (Stott et al, 1967;Flewett et al, 1974;Flewett, 1976;Madeley et al, 1977). This study did not include a group with no diarrhoea but it was conducted concurrently with a study of viruses isolated from children of the same age who were admitted with febrile convulsions (Lewis et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Rhinoviruses have been known for sometime to infect the upper respiratory tract (Tyrrell et al 1960). Though Portnoy, Eckert & Salvatore (1965) suggested rhinoviruses were of no aetiological significance in lower respiratory disease of childhood, Hilleman, Reilly, Stokes & Hamparian (1963) found that 'coryza viruses' (rhinoviruses) were associated with lower respiratory tract infection in a third of a small number of children investigated, and Stott et al (1967) found rhinoviruses in 7 % of children with acute lower respiratory infections. In this series, three rhinoviruses were isolated from NP secretions, but only two from CN swabs ( Table 2).…”
Section: Discussionmentioning
confidence: 99%